Opportunity costs of attending surgical clinic appointments and experiences with telemedicine for follow-up care. (September 2021) - Thatcher, Mitchell D; Thatcher, Michael W; Smith, Mckinley C; McCarron, Michelle; Reed, Jeremy
Objectives: Telemedicine has been rapidly implemented in orthopedics during the coronavirus (COVID-19) pandemic. The purpose of this study was to quantify opportunity costs for patients attending typical in-person appointments and understand their perceptions of telemedicine for follow-up care. Methods: A cross-sectional study was performed by surveying patients who had elective orthopedic surgery and attended at least one in-person and one phone call appointment. The survey assessed opportunity costs associated with in-person appointments, experience with telemedicine, and preferred type of future appointment. Results: Of the 49 eligible patients, 41 (83.7%) completed the survey. The median travel distance to the clinic was 108 km, and the time spent in the clinic was 60 min. Participants responded "yes" to various forms of opportunity costs associated with attending in-person appointments, including missed work (46.3%), lost income (34.1%), recreational activities (26.8%), home or yard care (14.6%), socializing with friends or family (12.2%), school (2.4%), and childcare (2.4%). In addition, elements of the telemedicine appointment were rated from 1 (least favorable) to 10 (most favorable), and averages were calculated for ease of use (9.2), convenience (8.4), confidence in the doctor's diagnostic ability (8.2), likelihood of using the service again (6.4), and overall satisfaction (8.2). Preferred future appointment types included having the first visit in-person and subsequent visits via telephone (61.0%), in-person only (36.6%), and unsure (2.4%). Conclusion: This study identifies various opportunity costs associated with in-person orthopedic appointments and a favorable view toward telemedicine for follow-up care.